How many extragalactic stellar mass binary black holes will be detected by space gravitational-wave interferometers?. Issue 4 (10th June 2022) - Seto, Naoki; Kyutoku, Koutarou
ABSTRACT: On the basis of GWTC-3, we discuss the detection prospect of extragalactic binary black holes (BBHs) by space gravitational-wave interferometers, mainly targeting BBHs in the range of chirp masses with abundant detections. In particular, we directly incorporate the chirp mass distribution of the 62 BBHs detected so far at high significance. We find that, due to the reduction of both the comoving merger rate and a weighted average of chirp masses, the expected detection numbers are generally much smaller than the results obtained by the same authors immediately after the report of GW150914. For LISA, the total BBH detections in the chirp mass range are estimated to be N tot ∼ 2( T /4yr) 3/2 (ρthr /10) −3, dominated by nearly monochromatic BBHs (ρthr : the detection threshold, T : the observational period). TianQin will have a total detection number N tot similar to LISA. Meanwhile, TianQin has potential to find N mer ∼ 0.6( T /4yr) 7/4 (ρthr /10) −3 BBHs that merge in the observational period. This number for merging BBHs is 4–5 times larger than that of LISA because of the difference of the optimal bands. We also investigate prospects for joint operations of multiple detectors, finding that concurrent observations will be more advantageous than sequential ones.